The Effect of Immigrant on Natives' School Achievement : Does Length of Stay in the Host Country Matter? - Bossavie, Laurent (World Bank, Washington, DC, 2018)
Using a rich data set of primary school students, this paper estimates the effects of immigrant concentration in the classroom on the academic achievement of natives. In contrast with previous contributions, it exploits rare information on age-at-migration to estimate separate spillover effects by duration of stay of immigrant classmates. To identify treatment effects, it uses cohort-by-cohort deviations in immigrant concentration within schools combined with attractive features of the Dutch school system. Overall, the paper finds no effect of the concentration of immigrant students on natives' test scores. However, although immigrant students who have been in the country for some time have virtually no effect on natives, the analysis finds a small negative effect of recent immigrants in the classroom on natives' test scores. This effect significant only for language test scores, but insignificant for mathematics test scores. When significant, effect sizes are quite small compared to other educational interventions and classroom peer effects estimated in other contexts.